Perubahan Kewenangan Juru Sita Dalam Pemanggilan Pihak Berperkara di Pengadilan Agama Sukadana - Hidayat, Riyan Erwin; Midia, Fredy Ghandi; Hidayatullah, Ahmad Manarul (Siyasah, 2023)
The discussion regarding bailiffs is currently interesting to discuss. Because there is a discourse that changes the bailiff's task system, namely in summoning litigants to court. Where summoning the parties to the case is one of the important duties of the bailiff. And in this case, the Supreme Court's discourse on changing the calling system via the post office means that it is clear that there are consequences to this policy. The aim of this research is to determine the impact that occurs when a litigant is summoned to the Religious Court using the Post Office. This research is field research, using qualitative data analysis. The results of the research carried out by transferring the parties' summons to a third party post office were not in accordance with the court's principles of simplicity, speed and low costs. Because it adds bureaucracy, the bailiff should contact the next litigant directly.